Pengembangan Perhiasan Tembaga Inspirasi Teknik Filigree Dengan Pendekatan Eksplorasi - Yayang Murdiyanto; Dedy Ismail (Jurnal Desain Indonesia., 2020)
Filigree jewelry has a complex and detailed jewelry character, so that market segmentation is limited to the middle and upper middle age range. This research plays an important role as one of the techniques and data collection methods that will be studied in the Design Project Course V. The purpose of developing the filigree technique with a new material approach is to expand market reach. In addition to the new material approach, the development of this filigree technique of jewelry design. The design research method used is data collection through observation, interviews, documentation, literacy studies and exploration. The results of this study indicate that filigree jewelry can develop according to trends and can reach a wider market segmentation so that it can add product value and quality of life of metal craftsmen.